Pengaruh Servant Leadership dan Lingkungan Kerja Terhadap Kinerja Pegawai pada Dinas Perumahan Kawasan Permukiman Pertanahan dan Lingkungan Hidup Kota Sawahlunto - Mega Oktari (Universitas Putra Indonesia YPTK Padang, 2022)
This study aims to analyze and find out how much influence Servant Leadership and Work Environment has on employee performance at the Housing Office of the Land and Environment Settlement Area of ​​Sawahlunto City with work motivation as an interfering variable. The method of collecting data is through surveys and distributing questionnaires, with a sample of 68 respondents. The analytical method used is validity and reliability test, path analysis, and multiple regression analysis, for hypothesis testing used t-test and F test using SPSS. The results of the study concluded that 1). There is a positive and significant influence of Servant leadership on work motivation. 2). There is a positive and significant effect of the work environment on work motivation. 3). There is a positive and insignificant effect of Servant leadership on employee performance. 4). There is a positive and significant effect of the work environment on employee performance. 5). There is a positive and insignificant effect of work motivation on employee performance. 6). Work motivation does not mediate Servant leadership on employee performance. 7). Work motivation does not mediate the work environment on employee performance